2013
DOI: 10.1103/physreva.88.035802
|View full text |Cite
|
Sign up to set email alerts
|

Drift of dark cavity solitons in a photonic-crystal fiber resonator

Abstract: International audienceWe consider a photonic crystal fiber resonator pumped by a coherent injected beam. We show that temporal cavity solitons exhibit a motion with a constant velocity. This regular drift is induced by a broken reflection symmetry mediated by a third-order dispersion. We focus the analysis on dark temporal cavity solitons. They consist of asymmetric moving dips in a uniform background of the intensity profile. The number of the moving dips and their temporal distribution are determined solely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…In the anomalous GVD regime it was shown that highorder chromatic dispersion effects can modify the dynamics and bifurcation structure of solitons in the LLE [24,25]. In particular, third-order dispersion (TOD) generates the emission of dispersive waves that can lead to the suppression of dynamical regimes such as oscillations and chaos [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In the anomalous GVD regime it was shown that highorder chromatic dispersion effects can modify the dynamics and bifurcation structure of solitons in the LLE [24,25]. In particular, third-order dispersion (TOD) generates the emission of dispersive waves that can lead to the suppression of dynamical regimes such as oscillations and chaos [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, spatial LS have been observed in laser systems where they arise from spontaneous emission noise [16,17] (active morphogenesis), without requiring an injected field. Because these lasing LS appear in a phase invariant system, their dynamical ingredients and their properties are very different from the LS appearing in injected resonators [18].Recent works have addressed the question whether the concept of LS can be extended to the time domain [19][20][21][22] in the case of optically injected cavities. Here we propose to answer to this question considering a phase invariant system, namely a passively mode-locked laser.…”
mentioning
confidence: 99%
“…We have described spatially localized structures, recent investigations have shown that temporal localized structures have been found in fibre resonators [104,90,105,106,107,108] and in VCSELS with a saturable absorber [109]. On the other hand, it has been shown that the combinated influence of diffraction and chromatic dispersion leads to the formation of three dimensional localized structures often called light bullet [110,111,112,113].…”
Section: Discussionmentioning
confidence: 99%